2013
DOI: 10.3390/proteomes1030275
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Unique Proteins in Human, Mouse and Rat Saliva Proteomes: Footprints of Functional Adaptation

Abstract: The overall goal of our study was to compare the proteins found in the saliva proteomes of three mammals: human, mouse and rat. Our first objective was to compare two human proteomes with very different analysis depths. The 89 shared proteins in this comparison apparently represent a core of highly-expressed human salivary proteins. Of the proteins unique to each proteome, one-half to 2/3 lack signal peptides and probably are contaminants instead of less highly-represented salivary proteins. We recently publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 26 publications
(68 reference statements)
3
27
0
Order By: Relevance
“…The mouse saliva proteome was previously published [13,14]. We provided the dialyzed and concentrated tear fluids to the University of Arizona Proteomics Core Facility where personnel determined the protein quantity in the samples and performed single-dimension (1D) SDS gel separations and two-dimension (2D; isoelectric focusing × SDS gel electrophoresis) gel separations of equal protein quantities for each gender.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse saliva proteome was previously published [13,14]. We provided the dialyzed and concentrated tear fluids to the University of Arizona Proteomics Core Facility where personnel determined the protein quantity in the samples and performed single-dimension (1D) SDS gel separations and two-dimension (2D; isoelectric focusing × SDS gel electrophoresis) gel separations of equal protein quantities for each gender.…”
Section: Methodsmentioning
confidence: 99%
“…The discovery and description of three large protein families that influence mouse communication have arisen from our studies of mouse Androgen-Binding Proteins (ABPs; [15]), studies of Exocrine Secreted Peptides (ESPs; [16]) and studies of Major Urinary Proteins (MUPs; [17,18]) by other laboratories. We show that these mouse protein families are represented to varying degrees in the mouse tear proteome (this report) and the mouse saliva proteome [13,14], and yet the studies cited above have shown that these protein families have no counterparts in humans. We discuss the possibility that some of the proteins unique to each secretion represent important adaptations of the mouse tear and saliva protein complements, especially with respect to mouse communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Muc19 alone has very little aggregating activity, Muc19 must participate indirectly to aggregate S. mutans, likely through formation of heterotypic complexes with other salivary constituents that bind S. mutans. At least 38 human salivary proteins (those with a predicted signal peptide) have orthologs or paralogs in saliva of mice and/or rats (103). Unique to human saliva are additional proteins, including statherin-like proline-rich proteins, histatins, lysozyme, zinc ␣-glycoprotein, and the Ig saliva secretory complex (103).…”
Section: Differences and Similarities In Expression Of Salivary Gelfomentioning
confidence: 99%
“…Unique to human saliva are additional proteins, including statherin-like proline-rich proteins, histatins, lysozyme, zinc ␣-glycoprotein, and the Ig saliva secretory complex (103). The 22 proteins unique to mice are thought to be involved mostly in wound healing, identification, or grooming (103).…”
Section: Differences and Similarities In Expression Of Salivary Gelfomentioning
confidence: 99%